Curcumin counteracts loss of force and atrophy of hindlimb unloaded rat soleus by hampering neuronal nitric oxide synthase untethering from sarcolemma. (8th May 2014) - Vitadello, Maurizio; Germinario, Elena; Ravara, Barbara; Libera, Luciano Dalla; Danieli‐Betto, Daniela; Gorza, Luisa
<x xml:space="preserve">Abstract</x> Key points Attenuation of disuse muscle atrophy by means of a pharmacological approach represents the wanted solution for patients who cannot exercise. Nutraceutics, e.g. the vegetal polyphenol curcumin, are relatively safe substances. By lowering oxidative stress, curcumin counteracted the loss of muscle mass and force of soleus muscles, reproduced in the laboratory rat by hindlimb unloading Curcumin effects are mediated by the chaperone protein Grp94, which maintains active neuronal nitric oxide synthase molecules at their physiological site in the skeletal myofibre. The systemic administration of very low doses of curcumin appears promising for counteracting muscle atrophy in bedridden patients. Abstract Antioxidant administration aimed to antagonize the development and progression of disuse muscle atrophy provided controversial results. Here we investigated the effects of curcumin, a vegetal polyphenol with pleiotropic biological activity, because of its ability to upregulate glucose‐regulated protein 94 kDa (Grp94) expression in myogenic cells. Grp94 is a sarco‐endoplasmic reticulum chaperone, the levels of which decrease significantly in unloaded muscle. Rats were injected intraperitoneally with curcumin and soleus muscle was analysed after 7 days of hindlimb unloading or standard caging. Curcumin administration increased Grp94 protein levels about twofold in muscles of ambulatory rats (P < 0.05) and antagonized its decrease in unloaded ones. Treatment countered loss of soleus mass and myofibre cross‐sectional area by approximately 30% (P ≤ 0.02) and maintained a force–frequency relationship closer to ambulatory levels. Indexes of muscle protein and lipid oxidation, such as protein carbonylation, revealed by Oxyblot, and malondialdehyde, measured with HPLC, were significantly blunted in unloaded treated rats compared to untreated ones (P = 0.01). Mechanistic involvement of Grp94 was suggested by the disruption of curcumin‐induced attenuation of myofibre atrophy after transfection with antisense grp94 cDNA and by the drug‐positive effect on the maintenance of the subsarcolemmal localization of active neuronal nitric oxide synthase molecules, which were displaced to the sarcoplasm by unloading. The absence of additive effects after combined administration of a neuronal nitric oxide synthase inhibitor further supported curcumin interference with this pro‐atrophic pathway. In conclusion, curcumin represents an effective and safe tool to upregulate Grp94 muscle levels and to maintain muscle function during unweighting.